Puzzling Pieces and Spiders' Webs: A Narrative about My Personal Journey to Teaching - Stephanie Burns (Networks: An Online Journal for Teacher Research, 2017)
I wrote the following paper upon completing my semester as a Student Teacher at an elementary school in a mid-size Midwestern university town. The goal in writing and presenting this paper was to select a focus area of growth throughout my time in the education program, considering how I’ve developed, what I’ve learned and where I hope to go as I continue forward on my journey of teaching and learning.